Analysis of implementation of green campus needs in education and research pillars at Edupark FKIP UNSRI - Azizah Husin; Yosef Yosef; Makmun Raharjo; Siti Dewi Maharani; Sri Sumarni (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
This study aims to analyze the needs of lecturers in implementing a green campus in the pillars of research and education at Edupark FKIP Unsri. The research method uses a qualitative approach with data collection techniques through Focus Group Discussions. The research subjects were lecturers and laboratory heads of each study program in the Ministry of Education (PAUD, PGSD, Community Education, and Guidance and Counseling). The study results show that there is still much that needs to be completed in Edupark FKIP Unsri as a complete standard of park criteria, including facilities: recreation, sports and outreach, as well as supporters and supporters and centres based on science study programs. Thus, research and educational activities can be carried out more optimally. It is suggested to faculty leaders to adapt better the planning process that is being made to the need to carry out research and teaching activities.